THU0562 Evolution of serum calprotectin in patients with juvenile idiopathic arthritis in clinical practice. (12th June 2018) - Magallares López, B.; Martínez-Martínez, L.; Hernandez-Lafuente, M.C.; Moltó, E.; Alvaro, Y.; Park, H.; Castellví, I.; Millán, M.; Díaz-Torné, C.; Moya, P.; Laiz, A.; Corominas, H.; et al.
Abstract : Background: Serum Calprotectin (MPR8/MPR14) is a promising biomarker in the management of juvenile idiopathic arthritis (JIA), mainly as a predictor of flare, especially in treatment de-escalation Objectives: To describe the evolution of serum Calprotectin in patients with JIA, their clinical evolution and its impact on therapeutic decisions Methods: Demographic, clinical and inflammatory activity data (RCP and ESR) were retrospectively collected in patients with JIA of any subtype in whom serum Calprotectin had been determined at least once Results: We present the data of 15 children, 7 with Oligoarticular subtype JIA, 1 Systemic, 3 Polyarticular, 1 Psoriasic and 3 Enthesitis Related Arthritis (ERA) The average age was 11 years, 66% female. The characteristics of each patient can be seen in table 1, together with the first determination of serum Calprotectin, CRP and ESR. It also shows the physiscan's decision, and the outcome, obtained from the assessment in the next visit Considering the cutoff point of serum Calprotectin in our sample of: 2.2 µg/mL (80% sensitivity and 69% specificity), 9 of 15 patients presented high values, 2 of them presented a flare (1 Oligo and 1 Poly), both had maintained the same treatment, because they were considered inactive. There were no flares in patients with negative Calprotectin The evolution of serum Calprotectin, together with the clinical decisions (based on clinical and analytical assessment) are described in table 1 In most of stable patients in whom serum calprotectin was high, it was decided not to lower treatment, and only in one case it was de-escalated. There were no flares in any of them Conclusions: Serum Calprotectin is a useful biomarker in routine clinical practice, together with other markers such as CRP and ESR, and our clinical judgment, it helps us to make therapeutic decisions Disclosure of Interest: None declared